Impact of mRNA and Inactivated COVID-19 Vaccines on Ovarian Reserve - Enes Karaman; Adem Yavuz; Erol Karakas; Esra Balcioglu; Busra Karaca; Hande Nur Doganay; Koray Gorkem Sacinti; Orhan Yildiz (Vaccines)
Objectives: This study aimed to elucidate the effects of messenger RNA (mRNA) and inactivated coronavirus disease 2019 (COVID-19) vaccines on ovarian histology and reserve in rats. Methods: Thirty female Wistar albino rats, aged 16–24 weeks, were randomly divided into three groups (n = 10): control, mRNA vaccine, and inactivated vaccine groups. Each vaccine group received two doses (on day 0 and day 28) at human-equivalent doses. Four weeks post-second vaccination, ovarian tissues were harvested for analysis. Results: Immunohistochemical analysis was performed to evaluate the expression of transforming growth factor beta-1 (TGF-β1), vascular endothelial growth factor (VEGF), caspase-3, and anti-Müllerian hormone (AMH) in ovarian follicles. Both vaccines induced significant increases in TGF-β1, VEGF, and caspase-3 expression, with more pronounced effects in the mRNA vaccine group. Conversely, AMH expression in the granulosa cells of primary, secondary, and antral follicles showed marked reductions (p < 0.001). The counts of primordial, primary, and secondary follicles decreased significantly in the inactivated vaccine group relative to controls and further in the mRNA vaccine group compared to the inactivated group (p < 0.001). Additionally, the mRNA vaccine group exhibited a decrease in antral and preovulatory follicles and an increase in atretic follicles compared to the other groups (p < 0.05). The serum AMH level was diminished with the mRNA vaccination in comparison with the control and inactivated groups. Conclusions: Our findings suggest that both mRNA and inactivated COVID-19 vaccines may detrimentally impact ovarian reserve in rats, primarily through accelerated follicular loss and alterations in apoptotic pathways during folliculogenesis. Given these observations in a rat model, further investigations into the vaccines’ effects on human ovarian reserve are needed.